Implementation of single-phase matrix converter as a controlled rectifier / Mohd Zulfadhli Mat Jusoh - Mat Jusoh, Mohd Zulfadhli (2004)
This thesis presents an implementation of single-phase matrix converter as a controlled rectifier by using digital microcontroller namely Peripheral Interface Controller as the main controller. The pulse-width-modulated control was used as an alternative approach to an earlier works that was found to be complex in nature in terms of control algorithm. Basically, there are various techniques in PWM control; the multiple-PWM is the one of various techniques in PWM control. The multiple-PWM technique was used in this project in order to control the output voltage of the converter. The PIC will generate this multiple-PWM in order to get the desirable output. The simulation of model SPMC as a rectifier was done by using MATLAB/Simulink and Pspice. Then the result of simulation is compared with the experimental result.